Avulsion of the Accessory-Carpal Ligaments and Sagittal Fracture of the Ulnar Carpal Bone in a Foal - Tatarniuk, Dane M.; White, Robin; Modesto, Rolf B.; Miles, Kristina G. (VCOT Open, 2019)
A 45-day-old foal presented for weight bearing lameness. Radiography revealed an abnormal radiolucent line associated with the proximal ulnar carpal bone and a separate curvilinear mineral opacity palmaromedial to the distal radial epiphysis. Computed tomography illustrated a sagittal, biarticular, non-displaced fracture of the ulnar carpal bone with small separate fragments associated with the accessory-ulnar and accessory-radial carpal ligaments. The foal was treated conservatively with rest and adjunct intra-articular hyaluronic acid. The lameness resolved within 90 days. Full range of motion of the carpus returned within 120 days following an active rehabilitation protocol. This report details avulsion of the accessory-carpal ligaments and sagittal fracture of the ulnar carpal bone secondary to presumed hyperextension injury.
Keywords: foal; orthopaedics; equine; fracture; carpus